2022
DOI: 10.1016/j.mayocpiqo.2021.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a Multispecialty Clinic for Patients with Central Sensitization–Based Chronic Pain Conditions

Abstract: Objective To design and evaluate, through a human-centered design approach, a multispeciality clinic for patients with central sensitization syndromes that combined virtual previsit consultations, traditional face-to-face appointments, and technology-enabled educational programming. Patients and Methods Patients with suspected fibromyalgia and chronic abdominal pain were seen in a multispecialty practice, and the performance of the clinic was evaluated against a contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As demonstrated in a meta-analysis, IBS patients had significantly higher anxiety and depression levels than controls ( p < 0.01) [ 39 ]. Another study showed that both anxiety and depression were predictors of the development of IBS, and IBS patients without anxiety and depression at baseline reported higher levels of these conditions at follow-up [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in a meta-analysis, IBS patients had significantly higher anxiety and depression levels than controls ( p < 0.01) [ 39 ]. Another study showed that both anxiety and depression were predictors of the development of IBS, and IBS patients without anxiety and depression at baseline reported higher levels of these conditions at follow-up [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“… 2 We developed eLearning content based on pain neuroscience education programming created for patients with fibromyalgia, 20 and was created as an extension of the multidisciplinary clinical effort described previously. 21 Five mHealth eLearning courses were created by multidisciplinary teams to focus on five centrally sensitized-based chronic pain conditions: fibromyalgia, post-COVID syndrome, chronic fatigue, irritable bowel syndrome, and chronic migraine. The in-person, virtual, and traditional paper-based patient education materials were digitized to include videos by multi-specialty providers, 8 animations, pictures, and interactive content, which incorporated neurobiology-based education that has been shown to improve symptom severity, pain catastrophizing, depression and anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…This information is used by allied health and nursing to arrange itineraries for on-site visits and to determine whether a patient may benefit from a virtual previsit. 3 Information is also requested regarding their social determinants of health. Our clinical teams use this information to understand the environment from which a patient arrives and to arrange for nonmedical services.…”
Section: Digital Care Horizonmentioning
confidence: 99%
“… 4 Once an episode of care is completed on site, our care teams also digitally extend patient support into the postvisit space through nurse-led individual and group educational programming. 3 These models extend the “episode of care” beyond the face-to-face visit advancing understanding of patient need, increasing visit efficiency, and supporting the patient through their medical journeys.…”
Section: Digital Care Horizonmentioning
confidence: 99%